Pulmonary artery hypertension in childhood: The transforming growth factor-β superfamily-related genes - Shi-Min Yuan (Elsevier, 2018)
Pulmonary artery hypertension (PAH) is very rare in childhood, and it can be divided into heritable, idiopathic drug- and toxin-induced and other disease (connective tissue disease, human immunodeficiency virus infection, portal hypertension, congenital heart disease, or schistosomiasis)-associated types. PAH could not be interpreted solely by pathophysiological theories. The impact of the transforming growth factor-β superfamily-related genes on the development of PAH in children remains to be clarified. Pertinent literature on the transforming growth factor-β superfamily-related genes in relation to PAH in children published after the year 2000 was reviewed and analyzed. Bone morphogenetic protein receptor type II gene mutation promotes cell division or prevents cell death, resulting in an overgrowth of cells in small arteries throughout the lungs. About 20% of individuals with a bone morphogenetic protein receptor type II gene mutation develop symptomatic PAH. In heritable PAH, bone morphogenetic protein receptor type II mutations may be absent; while mutations of other genes, such as type I receptor activin receptor-like kinase 1 and the type III receptor endoglin (both associated with hereditary hemorrhagic telangiectasia), caveolin-1 and KCNK3, the gene encoding potassium channel subfamily K, member 3, can be detected, instead. Gene mutations, environmental changes and acquired adjustment, etc. may explain the development of PAH. The researches on PAH rat model and familial PAH members may facilitate the elucidations of the mechanisms and further provide theories for prophylaxis and treatment of PAH. Key Words: bone morphogenetic proteins, mutation, pulmonary hypertension